Bacterial metabolism as responsible of beneficial effects of phytoestrogens on human health. Issue 11 (16th June 2020) - Peirotén, Ángela; Bravo, Daniel; Landete, José M.
Abstract: Phytoestrogens (PE) are compounds found in plants such as soy (isoflavones), flax seeds and cereals (lignans) and pomegranates (ellagitannins). PE have shown estrogenic/antiestrogenic, antioxidant, anti-inflammatory, antineoplastic and apoptotic activities. The human studies are showing promising although inconsistent results about the beneficial effects of PE on ameliorating the menopausal symptoms or reducing the risk of certain cancers, cardiovascular disease or diabetes. The effects of PE on the organism are mediated by the intestinal microbiota, which transforms them into bioactive PE such as genistein, equol, enterolignans and certain urolithins. In this work, we review the most recent findings about the bacteria able to metabolize PE, together with the latest studies on the effects of PE on health. In addition, we describe the possible factors hindering the demonstration of the beneficial effect of PE on health, evincing the importance of measuring the actual circulating PE in order to encompass the variability of PE metabolism due to the intestinal microbiota. With this in mind, we also explore an approach to ensure the access to bioactive PE.